Music adviser : emotion-driven music recommendation ecosystem - Rumiantcev, Mikhail (2017)
In respect of the big amounts of music available in the web, people met the problem of choice. From another side, practically unlimited resources can bring us new opportunities in the music context. Efficient data management engines which are smart and self managed are in demand nowadays in the music industry to handle music sources amounts of which are coming towards to infinity continuously. This study demonstrates feasibility of the emotional based personalization of music recommendation system. There is still gap between human and artificial intelligence, robotics do not have intuition and emotions which represent critical point of recommendations. Taking into account significant influence of music to human emotions, we can notice that it can be a strong chain between human emotions and machines. This work provides the novel implementation of the music recommendation system based on emotional personalization, which manages human emotions by selecting and delivering music tracks based on their previous personal listening experience, collaborative and classification filtering.